Infiltration in the Book al-Tafsîr al-Hadîth Works of ‘Izzat Darwazah; Analysis of the Meaning of the Verse Muhkamāt-Mutashabihāt - Solehodin, Solehodin (Islamic Religious Education Departement, 2023)
This article discussed Muhammed Izzat Darwazah’s thoughts in verse Muhkamāt-Mutashabihāt. This article was compiled based on the descriptive qualitative method. They are using library data as a type of Library research. As an analysis step, it uses the basis of comments from contemporary figures Abd Rahîm Fāris Abū Ulbah (b. 1947 AD-present). The results of this study are First, Through theory Muhkamāt-Mutashabihāt Darwazah tries to describe his new findings or make updates (Ihdath) draft. That is Concept Asās al-Qur’ān as an equation with Muhkamāt and aspects Wasā’il. (facilities/support) as an equation with Mutashabihāt. Second, In the theory of ta’wil, Darwazah is an adherent who allows to interpret verses that are Mutashabihāt even more freely because Darwazah uses his approach to Wasā’il. Third, in terms of infiltration (Dakhîl), many weaknesses were found in the theory of Wasā’il as stated by Darwazah (shawā’ib). Among them are not under the provisions of Muhkamāt-Mutashabihāt as agreed by the classical scholars. From a practical aspect, according to Abū Ulbah, it has a weakness. Namely, Darwazah’s theology is less consistent. He includes aspects of faith in Allah in the classification of verses Muhkamāt But on the other hand, in the element of faith, there is life after death, the Day of Judgment and the counter-events at the Last Day are classified under the theory Wasā’il or Mutashabihāt.